Tingkat Kecemasan Masyarakat Pada Saat Pandemi Covid-19 di Lingkungan VII, Kelurahan Padang Bulan Selayang I, Kecamatan Medan Selayang Tahun 2021 - Friska S.H. Ginting; Jagentar P. Pane; Sri Martini; Veronika Br. Ginting (STIKes Santa Elisabeth Medan, 2022)
Introduction: Covid-19 is an infectious disease caused by a new type of corona virus that was discovered in 2019. Currently, human-to-human spread has become the main transmission information so that the spread of this virus is very aggressive andthe spread was declared a pandemic.This makes people unprepared to face both physically and psychologically. One of the psychological conditions experienced by society is anxiety. Anxiety can be defined as a feeling of fear, worry and extreme nervousness. The purpose of this research isto identifythe level of public anxiety during the COVID-19 pandemic in neighborhood VII, Padang BulanSelayang I Village, Medan Selayang District.Method: The research method is a descriptive research method to identify “The level of public anxiety during the Covid-19 pandemic. Samples were taken using the Simple Random Sampling technique with a total of 79 respondent.Result:The results of data analysis showed that the majority of respondents had moderate anxiety levels, namely as many as 43 people (54.4%) and mild anxiety levels as many as 24 people (30.4%), severe anxiety levels were 11 people (13.9%), and a minority of respondents who had panic anxiety levels was 1 person (1.3%).Conclusion: Expectedthe community should always pay attention to and maintain the use ofhealth protocols when carrying out activities outside the home.